Potensi Interaksi Obat Pada Pasien Gangguan Lambung (Dispepsia, Gastritis, Tukak Peptik) Rawat Inap Di Rumah Sakit Keluarga Sehat Pati Tahun 2015 - Bagus Prakoso, Rinza; , Nurul Mutmainah, M.Si, Apt (2016)
Peptic ulcers is a formation of ulcus/ulcer in the upper gastrointestinal tract that caused by formation of acid and pepsin. There are 3 causes of gastrointestinal disorders, first that caused by helicobacter pylori, 2nd by consumption of non steroidal anti inflammatory drugs (NSAID), and then by mucosal damage associated with stress. Drugs interaction occur when the effect of medication change due to presence of the other drugs. Because of many adverse effect caused by the intraction, the installation of pharmacy at the hospital have to monitor the incidence of drug interaction. This study was conducted to determine potential of drug interactions in patient with peptic ulcers who hospitalized at Keluarga Sehat hospital in 2015. This study is non experimental study with retrospective data collection and analized descriptively. Sample collection was done by purposive sampling method. Data obtained as many as 97 samples. Then analyzed based on database http://www.drugs.com/drug_interactions.htm. The drugs most commonly used in prescription is proton pump inhibitor group (PPI), that is omeprazole. The PPI drugs are the first line therapy for patients with gastrointestinal disorder. The most common interaction that happen is the interaction with the pharmacodynamic equal to 51,5%. The interaction seen from the severity, the most common interaction that happened is a moderate level as much as 63,6%.